Gleason grading of prostate cancer: a pragmatic approach. Issue 10 (October 2019) - Short, Emma; Warren, Anne Y.; Varma, Murali
Abstract: The Gleason grading system that was initiated by a surgeon, created by a pathologist and developed by a statistician predated serum PSA testing, systematic 18-gauge needle biopsy protocols and immunohistochemistry. It has undergone a series of modifications, initially by Veterans Administration Cooperative Urological Research Group and later by the International Society of Urological Pathologists following consensus meetings in 2005 and 2014. This review focusses on selected areas of practical difficulty such as borderline grades, cores with different Gleason scores, reporting of percentage pattern 4 and minor high-grade patterns, intraductal carcinoma and the new grading system for prostate cancer. We offer a pragmatic guide to grading prostate carcinoma and explain how precision of grading becomes less important if the pathologist uses judgment to determine the Gleason score most suitable for that patient, communicates this data effectively in the report and helps clinicians interpret the information correctly.